Infinite ascent : a short history of mathematics - Berlinski, David, 1942- (New York : Modern Library, 2005)
Traces the history of mathematics over the course of 2,500 years, profiling ten important developments and figures, including Pythagoras, Euclid, Descartes, Leibniz, and Cantor.
Includes index.
Keywords: Mathematics -- History -- Popular works; Mathematics -- Philosophy -- History -- Popular works; Mathematicians -- History -- Popular works